Control familiarity bias when shifting to a risk-based approach: Lessons from the Temporary Traffic Management industry - Thomas, Jared; Malcolm, Louise; Thomas, Francene; Tate, Fergus; Frith, Bill; Burton, Joel (New Zealand Journal of Health and Safety Practice, 2025)
Risks are apparent in all industries, but what if the industry you worked in had been focussed on familiar, existing controls that didn’t eliminate risk? The Temporary Traffic Management (TTM) industry historically has had a culture that tends to accept risk, as working on or near roads carries an inherent level of risk. TTM worksites account for 66 serious and fatal injury crashes each year in New Zealand. To reduce incidents on worksites there has been a shift from prescriptive guidance to a risk-based approach, with the aim of moving to more impactful safety controls. A national TTM worker survey was created to review attitudes, reported behaviours on site, and the acceptance and adoption of a risk-based approach. Survey insights revealed that even in a higher-risk industry with a strong focus on workplace safety, engaged workers still have challenges to overcome. In the TTM context these were, correct identification of risk and appropriate controls, habituation to risk, and the pressure to balance and trade risk against competing requirements, like cost and delays to traffic. New insights indicate a Control Familiarity Bias (CFB), where controls that are available, familiar, easy and embedded are preferred, selected and assigned an overinflated weight in safety decisions, even where better alternatives exist.